Evaluation of Customer Service through PLN Mobile Application in the Framework of Electronic Government Maturity Model in Sidoarjo Customer Service Implementation Unit - Yulistiar, Fadhil Wahyu; Kriswibowo, Arimurti (Borong Newinera Publisher, 2024)
PT PLN (Persero) created the PLN Mobile application to improve the quality of service to customers with aspects of flexibility, convenience, speed, accuracy and transparency. However, in the Sidoarjo Customer Service Implementation Unit (UP3), there are still many customers who experience problems and submit complaints regarding the performance of the application. This study aims to evaluate PLN Mobile in UP3 Sidoarjo using the Electronic Government Maturity Model framework, namely the five pillars of Information Dissemination, Communication, Transactions, Interoperability, and Participation. This research method uses a qualitative case study to provide an in-depth description of the evaluation of customer service evaluation through the PLN Mobile application within the framework of the e-government maturity model in UP3 Sidoarjo. The results showed that several pillars, especially Transactions and Interoperability, have not been well fulfilled by PLN Mobile in UP3 Sidoarjo. The lack of integration with other services causes some services to be inaccessible through the application, forcing customers to come to the office. Therefore, the goal of PLN Mobile in improving service quality has not been fully achieved.